MODULATORY EFFECT OF CURCUMIN ON ENDOSULFAN INDUCED ANOMALIES IN THE KIDNEY FUNCTION OF MUS MUSCULUS - NIRUPAM, (The Bioscan, 2012)
The present study investigated the effect of curcumin on endosulfan induced anomalies in the kidney function of Mus musculus. Administration of endosulfan (3.0 mg/kg) resulted in marked increase in the values of blood urea (17.63%, 39.20% and 63.68%) and serum creatinine (20.37%, 44.64% and 105.55%) and reduction in the total protein concentration (5.14%, 16.20% and 29.13%) after 7, 14 and 28 d respectively. Analysis of variance showed that the level of blood urea and creatinine increased significantly (p≥0.05) from control however, the total protein concentration decreased significantly (p≥0.05) from control after 7, 14 and 28 d of endosulfan administration. The result also indicated that endosulfan induced anomalies in the kidney function was remarkably prevented by treatment with Curcumin. Curcumin restored renal function in Mus musculus as judged by the increase in total protein while decrease in blood urea and creatinine. These data suggest that administration of curcumin is a promising approach in the treatment of disturbed kidney function caused by endosulfan.